A Survey of Mobile Ad-Hoc Networks Based on Fuzzy Logic - Alameri, Ibrahim Ahmed Salman; Komárková, Jitka; Al-Hadhrami, Tawfik (Springer Nature Switzerland AG, 2023)
Wirelessly connected mobile devices with self-configuration need to have reliable communication. The deployment of routing techniques in dynamic Ad-Hoc networks has enhanced traffic management. In mobile Ad-Hoc networks (MANETs), each node freely moves from one place to another and acts as a router. However, mobile networks are also considered Ad-Hoc wireless networks. Wireless technologies are merged in MANETs to improve communication among the nodes. MANETs can be easily installed in civil and military applications. This paper presents a survey study on MANETs using fuzzy logic-based techniques based on reviewed literature. Also, some applications are discussed, which include forestry, search and rescue operations, and digital libraries. In addition, different types of routing protocols are incorporated, like proactive, reactive, hybrid, swarm intelligence, and fuzzy logic-based routing. However, a brief overview of fuzzy systems and different real-time applications that use fuzzy technology as a controller are given preference. Besides, investigating fuzzy logic in MANETs, especially in routing protocols, has attracted researchers to this field of study.
Průzkum mobilních ad-hoc sítí založených na fuzzy logice
Keywords: AODV; DSDV; Fuzzy Logic; MANETs; AODV; DSDV; Fuzzy Logika; MANETs